A Multi-Dimensional Model of Israeli Travelers’ Experience in Duty-Free Stores - Gavish, Iris; Gavish, Yossi; Shoham, Aviv (Advances in Social Sciences Research Journal, 2021)
Travelers’ duty-free shopping represents an under-researched consumption behavior with far reaching management and marketing implications. This study explores the extent to which three surface personality traits (impulsiveness, shopping involvement, and escapism) mediated by store atmosphere, store temptation, and shopping enjoyment, lead to buying in duty-free stores. A convenience sample of 163 Israeli adults in Israel’s Ben-Gurion International airport was used. A SEM-PLS model was used to analyze the relationships among the model’s constructs. The model supports the positive impacts of traits impulsiveness, shopping involvement, and escapism on buying behavior in duty-free stores, mediated by store atmosphere and store temptation (shopping enjoyment only affecting store temptation). A post-hoc analysis showed a positive relationship between store atmosphere and store temptation. This paper contributes to the literature by developing and testing an integrative model with important implications for tourism and hospitality industries. Deriving from the findings of this study, it behooves managers of stores and centers to promote the environmental sustainability aspects of the products sold in these stores.